2018
DOI: 10.1016/j.meatsci.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex and RYR1 gene mutation on the muscle proteomic profile and main physiological biomarkers in pigs at slaughter

Abstract: Gender and RYR1 gene mutation might have an effect on the muscle metabolic characteristics and on the animal's stress at slaughter, which could influence the process of muscle-to-meat conversion. Forty-eight pigs were distributed in a design including two factors: sex (male/female) and RYR1 genotype (NN/Nn). At slaughter, physiological blood biomarkers and muscle proteome were analyzed and carcass and meat quality traits were registered. Females had higher serum levels of glucose, urea, C-reactive protein "CRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…This fact can be explained as the effect of allele C on greater fatness and lower lean meat content. Many authors confirm our results (FIEDLER et al,1999;OTTO et al, 2007;CESAR et al, 2017;OLIVÁN et al,2018). CAST polymorphism Ser638Arg frequencies of genotypes did not differ significantly within all analyzed crossbreeds combination.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This fact can be explained as the effect of allele C on greater fatness and lower lean meat content. Many authors confirm our results (FIEDLER et al,1999;OTTO et al, 2007;CESAR et al, 2017;OLIVÁN et al,2018). CAST polymorphism Ser638Arg frequencies of genotypes did not differ significantly within all analyzed crossbreeds combination.…”
Section: Resultssupporting
confidence: 90%
“…The causal SNP was found in the RYR1 gene, which was related to malignant hyperthermia susceptibility in pigs (MA et al, 2012). This gene defect leads to changed membrane characteristics in the skeletal muscle fibres, especially to an increased release of calcium ions from the sarcoplasmic reticulum as a response to different stress factors (OLIVÁN et al, 2018). In pigs that carry allele T, FIEDLER et al (1999) reported increased diameters of the mean fibre types and increased glycolytic metabolic potential, lower pH value and higher drip loss.…”
Section: Introductionmentioning
confidence: 99%
“…There were also other possible causes indicated, like higher connective tissue content (as related to higher muscle collagen observed in EM [ 52 , 76 , 77 ]), differences in carcass cooling rates (as associated to lower fat cover or/and intensity of post-mortem muscle metabolism in EM). However, as to the recently performed research, measuring carcass temperatures after slaughter did not indicate differences between the different sex categories at conventional carcass weights and cooling procedures [ 50 , 78 ]. Conversely, the study of Caldara et al [ 64 ], indicated higher internal carcass temperatures in SC compared to IC due to thicker carcass fat in the former, but the differences were relatively small and without influence on meat quality.…”
Section: Fat and Meat Qualitymentioning
confidence: 93%
“…Similarly, higher pH and DFD were observed when EM were held overnight after transport before slaughter in comparison to SC [ 46 ]. Newer studies, however, demonstrated no differential response to stress (EM vs. IC or SC [ 47 , 48 ] and IC vs. SC [ 49 ]) or even lower stress response of EM in comparison to gilts [ 50 ] or SC [ 39 ], with little or no notable effect on meat quality [ 22 , 48 ]. It is, however, worth noting here, that the mentioned results refer to different levels and duration of stress (either chronic or acute), which may have very divergent effects on the animal physiology [ 51 ].…”
Section: Fat and Meat Qualitymentioning
confidence: 99%
“…Genetic selection of broilers for fast growth rates and higher breast yields is accompanied with an increased susceptibility to stress‐related myopathy, including deep pectoral myopathy and PSE‐like meat, and the recently discovered white‐striping and wooden‐breast (Petracci et al., ). Furthermore, the mutations in the myostatin and calpain system of ruminants have direct relationships with meat tenderness (Warner, Greenwood, Pethick, & Ferguson, ), and more recently, the ryanodine receptor (RyR)1 mutation of pigs has been correlated with muscle fiber characteristics and postmortem glycolysis (Oliván et al., ).…”
Section: Stress Factors That Affect Meat Qualitymentioning
confidence: 99%